The value of dehydrated alfalfa and delayed grain feeding of heifers on winter bluestem pasture - Hall, M.C.; Smith, E.F.; Spies, H.G. (Kansas Agricultural Experiment Station, 2011)
Two primary objectives of this test were to: (1) Compare dehydrated alfalfa with soybean oil meal as a winter supplemental feed on bluestem pasture for heifer calves to be bred shortly after the winter feeding period. (2) Determine merit in feeding grain the last 30-40 days of the winter period compared with feeding the same total amount of grain throughout the winter where heifers are to be bred shortly after the winter feeding period terminates. Each of three treatment groups contained 27 or 28 Hereford heifer calves, good to choice grade. Initial average weight was 427 pounds.
Keywords: Beef; Alfalfa; Heifers; Bluestem pasture; Soybean oil